2005
DOI: 10.1242/jcs.02501
|View full text |Cite
|
Sign up to set email alerts
|

Role of the spindle-pole-body protein ApsB and the cortex protein ApsA in microtubule organization and nuclear migration in Aspergillus nidulans

Abstract: Nuclear migration and positioning in Aspergillus nidulans depend on microtubules, the microtubule-dependent motor protein dynein, and auxiliary proteins, two of which are ApsA and ApsB. In apsA and apsB mutants nuclei are clustered and show various kinds of nuclear navigation defects, although nuclear migration itself is still possible. We studied the role of several components involved in nuclear migration through in vivo fluorescence microscopy using fluorescent-protein tagging. Because ApsA localizes to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
76
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(82 citation statements)
references
References 65 publications
4
76
0
1
Order By: Relevance
“…Compared to he wild type (SJW02), the number of MTs was reduced in the ⌬alpA strain. Basically, only one thick MT bundle (according to Veith et al [27]), connecting adjacent nuclei, was visible, in addition to some shorter MTs emerging from the nuclear spindle pole bodies, while in the wild-type strain several single and bundled MTs were present (Fig. 5A, B).…”
Section: Alpa Localizes To Mt Plus Ends During Mitosis and In Interphmentioning
confidence: 81%
See 1 more Smart Citation
“…Compared to he wild type (SJW02), the number of MTs was reduced in the ⌬alpA strain. Basically, only one thick MT bundle (according to Veith et al [27]), connecting adjacent nuclei, was visible, in addition to some shorter MTs emerging from the nuclear spindle pole bodies, while in the wild-type strain several single and bundled MTs were present (Fig. 5A, B).…”
Section: Alpa Localizes To Mt Plus Ends During Mitosis and In Interphmentioning
confidence: 81%
“…However, it has to be noted that dynein mutants of A. nidulans do not display the same hyphal growth phenotype. In addition, dynein-mediated MT-cortical interactions are required for nuclear migration and nuclear positioning (27). Both phenomena were not affected in alpA mutants.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have shown that proper nuclear distribution first requires the active migration of nuclei, followed by the anchoring of nuclei to the cytoplasm microtubule and then their attachment to the plasma membrane (44,50,51). During this process, microtubule organization, actin cytoskeleton, and motor proteins play important roles; thus, blocking any of their components results in abnormal nuclear trafficking and nuclear distribution (3,32,50,51).…”
Section: Discussionmentioning
confidence: 99%
“…Once the plus-ends of astral microtubules bind to Num1, they slide against the cell cortex in a dynein-mediated manner which moves the spindle and eventually the daughter nucleus into the newly formed bud (Heil-Chapdelaine et al 2000). Functional homologs of Num1 are also required for proper nuclear migration in multinucleate fungi, including A. nidulans (Veith et al 2005) and Ashbya gossypii (Grava et al 2011). In M. oryzae , a Num1 homolog, MoAND1, has been characterised (Jeon et al 2014).…”
Section: Nuclear Migration During Plant Infectionmentioning
confidence: 99%